2013
DOI: 10.17269/cjph.104.3998
|View full text |Cite
|
Sign up to set email alerts
|

Energy Drink Consumption and Associations With Demographic Characteristics, Drug Use and Injury Among Adolescents

Abstract: , a 16% increase over the previous year. 2 Caffeine is the primary active ingredient in energy drinks, but the level of caffeine content varies widely across the many brands sold. 1,3 The caffeine content per 250 mL of an energy drink is usually 80-140 mg or the equivalent of two cans of cola or a 6-oz to 8-oz cup of coffee. [3][4][5] There are, however, energy drinks with caffeine content of up to 500 mg per can. 3,4 Additional ingredients include amino acid, vitamins, herbs, and other supplements purported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 21 publications
7
41
2
3
Order By: Relevance
“…These estimates of ED use are similar to prevalence rates reported in a few samples of high school students in North America (Hamilton et al, 2013;Kumar et al, 2014;Terry-McElrath et al, 2014). One possible explanation for this high rates is that ED might be regarded by some students as safer, more normative, or more socially acceptable than using illicit ''street'' drugs, perhaps because they think of EDs as being both legal to purchase and ostensibly safe to use (Arria et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…These estimates of ED use are similar to prevalence rates reported in a few samples of high school students in North America (Hamilton et al, 2013;Kumar et al, 2014;Terry-McElrath et al, 2014). One possible explanation for this high rates is that ED might be regarded by some students as safer, more normative, or more socially acceptable than using illicit ''street'' drugs, perhaps because they think of EDs as being both legal to purchase and ostensibly safe to use (Arria et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…Weekly or daily ED consumption was strongly associated with alcohol dependence . Consistent with these findings gained from university populations, recent survey studies conducted among high school students in Canada (Hamilton et al, 2013; and America (Terry-McElrath et al, 2014) suggested a strong association between ED consumption and substance use. Several studies also suggest that caffeine (Collins et al, 1997;Pallanti et al, 2006) and caffeine containing EDs (Reissig et al, 2009;Arria et al, 2008) may serve as a gateway to other forms of drug dependence.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Although recent nationwide data on energy drink consumption are scarce, some researchers estimate that over 18% of young adults consume energy drinks at least weekly, 2 and, among college students, this percentage may be as high as 39%. 3 Emerging evidence points to a relationship between energy drink use and various risk behaviors, including alcohol abuse, 2-10 cigarette smoking, 2,6-9,11-13 illicit drug use, 2,6-9,11-13 nonmedical use of prescription drugs, 5,6,8,11,14 fighting, 8 and sexual risk behavior. 8 One of the primary aims of this study was to replicate and extend these findings.…”
Section: Introductionmentioning
confidence: 99%